Recent advances in hypersensitivity pneumonitis - Lacasse, Yves; Girard, Mélissa; Cormier, Yvon (Chest, 2012)
Hypersensitivity pneumonitis (HP) is a pulmonary disease with symptoms of dyspnea and cough resulting from the inhalation of an allergen to which the subject has been previously sensitized. The diagnosis of HP most often relies on an array of nonspecific clinical symptoms and signs developed in an appropriate setting, with the demonstration of interstitial markings on chest radiographs, serum precipitating antibodies against offending antigens, a lymphocytic alveolitis on BAL, and/or a granulomatous reaction on lung biopsies. The current classification of HP in acute, subacute, and chronic phases is now challenged, and a set of clinical predictors has been proposed. Nonspecific interstitial pneumonitis, usual interstitial pneumonia, and bronchiolitis obliterans organizing pneumonia may be the sole histologic expression of the disease. Presumably, like in idiopathic interstitial pneumonia, acute exacerbations of chronic HP may occur without further exposure to the offending antigen. New offending antigens, such as mycobacteria causing hot tub lung and metalworking fluid HP, have recently been identified and have stimulated further research in HP.